Host-Pathogen Interactions: Insects vs Fungi - Dubovskiy, Ivan M. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Although many insects successfully live in dangerous environments exposed to diverse communities of microbes, they are often exploited and killed by specialist pathogens. In the process of the co-evolution of insects and entomopathogenic microorganisms, they develop various adaptive systems that determine the sustainable existence of dynamic host-parasite interactions at both the organismic and population levels.